Defining Misprescribing to Inform Prescription Opioid Policy - Dineen, Kelly K. (The Hastings Center report, 2018)
Prescription opioid policies too often reflect over a century's worth of moralizing about the nature of opioid use disorder, the value of pain, and the meaning of suffering. The social and legal penalties to prescribers run in one direction—avoid overprescribing, however defined, at all costs. The lack of shared definitions is problematic for formulating and evaluating opioid policy. For example, the variant definitions of “misuse,” “abuse,” and “addiction” complicate estimates of morbidity. There are also no widely accepted definitions of misprescribing and overprescribing. I offer here a modest attempt at the categorization of misprescribing: inadvertent overprescribing, corrupt overprescribing, qualitative overprescribing, quantitative overprescribing, multiclass overprescribing, and underprescribing.